1984
DOI: 10.1002/ar.1092090210
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of cultured palatal shelves from alligator, chick, and mouse embryos

Abstract: Palatal shelves from embryonic alligators, chicks, and mice were explanted at various stages of development and organ cultured in either chemically defined, serumless media or the same media supplemented with 10% fetal calf serum. Shelves from each vertebrate were either cultured singly or in contact, and heterologous combinations of palatal shelves from different animals were made: chick/mouse, chick/alligator, and mouse/alligator. Epithelial differentiation (particularly that of the medial shelf edge) was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 33 publications
(56 reference statements)
0
21
0
1
Order By: Relevance
“…The mere isolation of developmentally relevant coding sequences from reptiles will provide a muchneeded missing link. Oviparous species such as alligator and turtle offer opportunities for in ovo fate mapping, setting up organ cultures (inter or homospecific; Ferguson et al, 1984;Nagashima et al, 2005) or for performing experimental manipulations in ovo. Interspecific grafts would allow one to test whether conservation of tissue interactions and gene function exists between the major amniote groups.…”
Section: An Earlier Start To Bone Morphogenesis-being At the Right Plmentioning
confidence: 99%
“…The mere isolation of developmentally relevant coding sequences from reptiles will provide a muchneeded missing link. Oviparous species such as alligator and turtle offer opportunities for in ovo fate mapping, setting up organ cultures (inter or homospecific; Ferguson et al, 1984;Nagashima et al, 2005) or for performing experimental manipulations in ovo. Interspecific grafts would allow one to test whether conservation of tissue interactions and gene function exists between the major amniote groups.…”
Section: An Earlier Start To Bone Morphogenesis-being At the Right Plmentioning
confidence: 99%
“…During mammalian palate development, the initially vertically oriented palatal shelves are often in direct contact with but do not normally adhere to the mandible or the developing tongue (Shapiro and Sweney, 1969;Mato and Uchiyama, 1975;Ferguson et al, 1984). Pathological palatemandible and palate-tongue fusions, however, have been reported in humans, mice, and rats (Humphrey, 1970;Mato and Uchiyama, 1975;Shah, 1977;Jiang et al, 1998;Din, 2003;Alappat et al, 2005), suggesting that the competence for oral and palatal shelf adhesion must be spatiotemporally regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Following contact, the two medial edge epithelial sheets merge to form the MEE seam that will soon undergo degeneration (Ferguson 1988;Shuler et al, 1991;Shuler et al, 1992;Carette and Ferguson 1992;Griffith and Hay 1992;Murray and Schutte, 2004). This process requires the differentiation of palatal medial edge epithelial cells that are distinct from the epithelial cells on oral and nasal sides (Ferguson et al, 1984). Moreover, tissue recombination experiments revealed that the differentiation of medial epithelial cells is determined by the underlying medial edge mesenchymal cells (Ferguson et al, 1984).…”
mentioning
confidence: 99%